Dual Functionalization of Liquid‐Exfoliated Semiconducting 2H‐MoS2 with Lanthanide Complexes Bearing Magnetic and Luminescence Properties. (8th September 2017) - McAdams, Simon G.; Lewis, Edward A.; Brent, Jack R.; Haigh, Sarah J.; Thomas, Andrew G.; O'Brien, Paul; Tuna, Floriana; Lewis, David J.
Abstract: Liquid exfoliated, atomically thin semiconducting transition metal dichalcogenides (TMDs), as inorganic equivalents of graphene, have attracted great interest due to their distinctive physical, optoelectronic, and chemical properties. Functionalization of 2D TMDs brings new prospects for applications in optoelectronics, quantum technologies, catalysis, and medicine. In this report, dual functionalization of 2D semiconducting 2 H ‐MoS2 nanosheets through simultaneous incorporation of magnetic and luminescent properties is demonstrated. A facile method is proposed for tuning the properties of the TDM semiconductors and accessing multimodal platforms, consisting in covalent grafting of lanthanide complexes onto the surface of 2D TMDs. Dual functionalization of liquid‐exfoliated MoS2 nanosheets is demonstrated simultaneously with both europium (III) and gadolinium (III) complexes to form a colloidally stable luminescent (with millisecond lifetimes) and paramagnetic MoS2 ‐based nanohybrid material. This work is the first example of transition metal dichalcogenide nanosheets functionalized with preformed lanthanide complexes. These findings open new prospects for covalent functionalization of TMDs with molecular species bearing specific functionalities as a means to tune the optoelectronic properties of the semiconductors, in order to create advanced materials and devices with a wide range of functionalities. Abstract : Semiconducting 2 H ‐MoS2 nanosheets are functionalized simultaneously with europium (III) and gadolinium (III) complexes. The characteristic optical and paramagnetic behavior of the lanthanides is maintained postfunctionalization, in addition to the semiconductor phase of the 2 H ‐MoS2 . This work brings new and added functionality to MoS2 without resorting to refractory doping, thinning to monolayer, or other approaches.